ROMANTISASI BIAS GENDER RUMAH TANGGA DALAM LAGU "MENDUNG TANPO UDAN" - Adenisa Nurul Fathimah; Fela Liana; Ardana Kartika Sari (Jurnal Ilmu Komunikasi Acta Diurna, 2023)
The song "Mendung Tanpo Udan" is a piece of pop music created by Kukuh Prasetya Kudamai and arranged by Ndarboy Genk into dangdut style. The researcher analyzed the song "Mendung Tanpo Udan" because this song contains lyrics that represent gender-based injustice in the context of mass and digital communication. Based on the descriptive-qualitative research method with content analysis techniques, the researchers got the results that the song "Mendung Tanpo Udan" resembles a form of gender-based injustice in the form of stereotyping the positions of men and women, especially in the division of household roles. Stereotyping comes from gender differences that are displayed in society as a result of various things, including being formed, socialized, and strengthened into a social construction. When culture or belief in society considers gender differences as the nature of men and women, then a form of gender injustice occurs, such as the effort to romanticize the bias of the husband-wife position in the song "Mendung Tanpo Udan" which has won massive praise. There is a form of gender-based injustice romanticization by a song that is popular in the mass and digital media, proving the audience's insensitivity to the issue of gender-based injustice, which in this case harms the position and role of women.